Decision - making, legitimation, and power in Hot Bench - Mohd Muzhafar Idrus; Tun Nur Afizah Zainal Ariff; Harison@Hanisa Mohd Sidek; Hazleena Baharun (Universiti Sains Islam Malaysia, 2024)
Non-Indexed Publication